Rational design of cobalt oxide nanocubes arrays on Ni foam as durable and robust electrocatalyst for urea electro-oxidation - Mona M. Ismail; Ahmed A. Farghali; Ahmed G. El-Deen (Beni-Suef University Journal of Basic and Applied Sciences, 2024)
Abstract Background Cobalt oxide (Co3O4) is a promising electrocatalyst for efficient urea electro-oxidation, tackling power consumption and environmental challenges. The controllable design of free-standing Co3O4 nanostructures grown on Ni foam (NF) substrates was achieved using a green and facile hydrothermal approach. Different reducing agents were applied to synthesize various morphological structures of Co3O4, including nanoparticles, nanowires, and nanocubes (NCs) morphologies. Results The as-fabricated electrodes were investigated as electrocatalysts for enhanced urea electro-oxidation. Because of its 3D nanostructure with minimal agglomeration and a large interfacial surface area with adequate electroactive sites, the Co3O4 NCs/NF had the best energy conversion efficiency of any electrode toward the urea oxidation process. These distinctive features facilitated the electron and urea routes used in the urea electro-oxidation process. It had a low-onset potential of 194.2 mV (vs. Hg/HgO) and a current density of 90.2 mA cm−2 in a 1 M KOH electrolyte. The electrocatalyst demonstrated excellent anodic activity for urea electro-oxidation with an onset potential of 196.7 mV and a current density of 256.1 mA cm−2 in 1 M KOH + 0.3 M urea concentration. Furthermore, the Co3O4 NCs/NF exhibited long-term stability, as shown by chronoamperometry and stepwise tests after 3600 s in the presence of urea under various operating conditions. Conclusions Compared to all the fabricated Co3O4 nanostructures, the Co3O4 nanocubes revealed the highest electrocatalytic performance toward urea electro-oxidation in all concentrations. Therefore, Co3O4 NCs/NF is a promising, robust, and efficient electrocatalyst for direct urea fuel cell applications.